Aspek Hubungan Dewan Perwakilan Rakyat dan Presiden dalam Pembahasan Bersama Suatu Undang-Undang - Ichsan Anwary (Faculty of Law, Maranatha Christian University, 2015)
The term â€œholding authorityâ€ according to Article 20 (1), Constitution of 1945, Indonesia means as an obligation. House of Representative holding authority to establish laws refer to a its authority to propose Draft of Laws.Formulation or construction concerning on authority on establishing laws, which regards to three state institutions: House of Representative, President and Regional Representative Council is not designed in a complete and best design.